IMPROVING THE QUALITY AND EFFICIENCY OF TEACHING FOREING LANGUAGE (ENGLISH) IN PRE-SCHOOL EDUCATIONAL INSTITUTIONS - Khidoyatov, Nusratilla Shavkatilla ugli; Rasulova, Dilbar (Educational Research in Universal Sciences, 2024)
This article discusses the importance of teaching foreign languages in Uzbekistan and the ways in which English language teaching methods are used to improve their effectiveness in pre-school institutions.